Acquired antibody responses against Plasmodium vivax infection vary with host genotype for duffy antigen receptor for chemokines (DARC). - Amanda Maestre; Carlos Muskus; Victoria Duque; Olga Agudelo; Pu Liu; Akihide Takagi; Francis B Ntumngia; John H Adams; Kim Lee Sim; Stephen L Hoffman; Giampietro Corradin; Ivan D Velez; et al. (PLoS ONE)
Background Polymorphism of the Duffy Antigen Receptor for Chemokines (DARC) is associated with susceptibility to and the severity of Plasmodium vivax malaria in humans. P. vivax uses DARC to invade erythrocytes. Individuals lacking DARC are 'resistant' to P. vivax erythrocytic infection. However, susceptibility to P. vivax in DARC+ individuals is reported to vary between specific DARC genotypes. We hypothesized that the natural acquisition of antibodies to P. vivax blood stages may vary with the host genotype and the level of DARC expression. Furthermore, high parasitemia has been reported to effect the acquisition of immunity against pre-erythrocytic parasites. We investigated the correlation between host DARC genotypes and the frequency and magnitude of antibodies against P. vivax erythrocytic stage antigens. Methodology/findings We assessed the frequencies and magnitudes of antibody responses against P. vivax and P. falciparum sporozoite and erythrocytic antigens in Colombian donors from malaria-endemic regions. The frequency and level of naturally-acquired antibodies against the P. vivax erythrocytic antigens merozoite surface protein 1 (PvMSP1) and Duffy binding protein (PvDBP) varied with the host DARC genotypes. Donors with one negative allele (FY*B/FY*Bnull and FY*A/FY*Bnull) were more likely to have anti-PvMSP1 and anti-PvDBP antibodies than those with two positive alleles (FY*B/FY*B and FY*A/FY*B). The lower IgG3 and IgG1 components of the total IgG response may account for the decreased responses to P. vivax erythrocytic antigens with FY*A/FY*B and FY*B/FY*B genotypes. No such association was detected with P. falciparum erythrocytic antigens, which does not use DARC for erythrocyte invasion. Conclusion/significance Individuals with higher DARC expression, which is associated with higher susceptibility to P. vivax infection, exhibited low frequencies and magnitudes of P. vivax blood-stage specific antibody responses. This may indicate that one of the primary mechanisms by which P. vivax evades host immunity is through DARC indirectly down-regulating humoral responses against erythrocytic invasion and development.